Implementation of Aceh Local Wisdom-Based Education Program at MTsN 5 Pidie, Pidie Regency - Efi Mulyati; Rahmi Novalita; Rambang Muharramsyah (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
This type of research is exploratory qualitative. The informants of this research are teachers of MTsN 5 Pidie, Pidie Regency. The informant selection technique uses snowball sampling technique. Data collection techniques use observation, interviews and documentation. Data validity techniques use credibility, transferability, dependability, confirmability. Data analysis techniques use data reduction, data display, data interpretation, and conclusion drawing. The results of the study indicate that; MTsN 5 Pidie, Pidie Regency has implemented an education program based on Acehnese local wisdom well. Forms of educational activities based on Acehnese local wisdom at MTsN 5 Pidie include: Integration of local culture into subjects, such as mathematics linked to the architecture of Acehnese traditional houses, Pancasila and citizenship education linked to the values ​​of deliberation and khanduri customs, economics contextualized through farming practices and kenduri blang, as well as the use of teaching materials in the form of poetry, pantun, and Acehnese folklore. Arts and cultural activities include training in the Saman and Seudati dances, traditional Rapa'i music, folk games, Acehnese poetry readings, and traditional Acehnese handicrafts. Extracurricular activities include cooking classes on Acehnese cuisine, such as plik u soup and various other traditional dishes, cultural festivals, and afternoon innovation classes.